Dental anomalies of the deciduous dentition among Indian children: A survey from Jodhpur, Rajasthan, India - Shravani Govind Deolia; Chaya Chhabra; Kumar Gaurav Chhabra; Shrivardhan Kalghatgi; Naresh Khandelwal (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2015)
Background: Anomalies and enamel hypoplasia of deciduous dentition are routinely encountered by dental professionals and early detection and careful management of such conditions facilitates may help in customary occlusal development. Objective: The aim of this study was to determine the prevalence of hypodontia, microdontia, double teeth, and hyperdontia of deciduous teeth among Indian children. Materials and Methods: The study group comprised 1,398 children (735 boys, 633 girls). The children were examined in department of Pedodontics and Preventive Dentistry in Jodhpur Dental College General Hospital, Jodhpur, Rajasthan, India. Clinical data were collected by single dentist according to Kreiborg criteria, which includes double teeth, hypodontia, microdontia, and supernumerary teeth. Statistical analysis of the data was performed using the descriptive analysis and chi-square test. Results: Dental anomalies were found in 4% of children. The distribution of dental anomalies were significantly more frequent (P = 0.001) in girls (5.8%, n = 38) than in boys (2.7%, n = 18). In relation to anomaly frequencies at different ages, significant difference was found between 2 and 3 years (P = 0.001). Conclusion: Double teeth were the most frequently (2.3%) observed anomaly. The other anomalies followed as 0.3% supernumerary teeth, 0.6% microdontia, 0.6% hypodontia. Identification of dental anomalies at an early age is of great importance as it prevents malocclusions, functional and certain psychological problems.